(untitled) (Cultura Económica, 2018)
In 1997, the Federal Council of Education published a resolution according to which the children of the Mennonite community settled in the province of La Pampa had to leave aside the traditional education proposed by their community, and embrace the official Argentine teaching system. Despite the fact that the case is a few years old, the debate arises again with regard to sex education, given that the Government should guarantee an education that may be free of any particular worldview. Then, we could not face comprehensive sexual education under any particular theory or worldview, but only from scientific and secular criteria.